2014
DOI: 10.1073/pnas.1317065111
|View full text |Cite
|
Sign up to set email alerts
|

High carbon dioxide uptake by subtropical forest ecosystems in the East Asian monsoon region

Abstract: Temperate-and high-latitude forests have been shown to contribute a carbon sink in the Northern Hemisphere, but fewer studies have addressed the carbon balance of the subtropical forests. In the present study, we integrated eddy covariance observations established in the 1990s and 2000s to show that East Asian monsoon subtropical forests between 20°N and 40°N represent an average net ecosystem productivity (NEP) of 362 ± 39 g C m −2 yr −1 (mean ± 1 SE). This average forest NEP value is higher than that of Asia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
226
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 452 publications
(262 citation statements)
references
References 43 publications
5
226
0
2
Order By: Relevance
“…At each site, the meteorological variables including solar radiation, air temperature and relative humidity were measured at a frequency of 2 s and then recorded at 30-min intervals. Further details of the monitoring systems were presented by Chen et al (2013) and Yu et al (2014).…”
Section: Data Observation and Process Of Chinafluxmentioning
confidence: 99%
“…At each site, the meteorological variables including solar radiation, air temperature and relative humidity were measured at a frequency of 2 s and then recorded at 30-min intervals. Further details of the monitoring systems were presented by Chen et al (2013) and Yu et al (2014).…”
Section: Data Observation and Process Of Chinafluxmentioning
confidence: 99%
“…In general, the NPP was regarded as the material basis of aboveground and belowground biomass in plant communities, whereas the NEP was directly defined as the net carbon sequestration of natural ecosystems and was considered the climate-based potential carbon source/ sink in the absence of anthropogenic and natural disturbances [26].…”
Section: Nep and Carbon Fluxes Of Major Natural Processes In Ecosystemsmentioning
confidence: 99%
“…Currently, the methods used in the determination of ecosystem productivity and the evaluations of the carbon budget at different spatial and temporal scales include eddy covariance [11], resource inventory [12,13], airborne laser scanning [14], remote sensing evaluation based on resource satellite observations [15], remote sensing inversion of carbon satellites [16,17], geographical statistical modeling [18,19], analysis based on process-based models [20][21][22] and atmospheric inversion [23,24]. These technologies have improved continually with their own appropriate spatiotemporal scales, and researchers have also performed meta-analyses based on multi-source data from different approaches [25,26]. Additionally, comprehensive assessments were conducted on the ecosystem productivity or carbon source/sinks at national, continental and global scales by data-model fusion [7,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Global analysis of carbon fluxes indicated that East Asian monsoon subtropical forests between 20°N and 40°N have high strength of carbon uptake and it attributes to the combined effects of the young stand ages, high nitrogen deposition and sufficient and synchronous water and heat availability ( Yu et al, 2014c). Integrative analysis of global carbon fluxes data showed that GPP and RE co-varied at the spatial pattern from regional to global scale (Yu et al, 2013b;Chen et al, 2013;Chen et al, 2015b) .…”
Section: High Carbon Sinks and Interrelations Among Carbon Fluxes At mentioning
confidence: 99%